Cannabidiol Limits T Cell-Mediated Chronic Autoimmune Myocarditis: Implications to Autoimmune Disorders and Organ Transplantation - Wen-Shin Lee; Katalin Erdelyi; Csaba Matyas; Partha Mukhopadhyay; Zoltan V Varga; Lucas Liaudet; György Haskó; Daniela Čiháková; Raphael Mechoulam; Pal Pacher (BMC, 2016)
Abstract Myocarditis is a major cause of heart failure and sudden cardiac death in young adults and adolescents. Many cases of myocarditis are associated with autoimmune processes in which cardiac myosin is a major autoantigen. Conventional immunosuppressive therapies often provide unsatisfactory results and are associated with adverse toxicities during the treatment of autoimmune myocarditis. Cannabidiol (CBD) is a nonpsychoactive constituent of marijuana that exerts antiinflammatory effects independent of classical cannabinoid receptors. Recently, 80 clinical trials have investigated the effects of CBD in various diseases from inflammatory bowel disease to graft versus host disease. CBD-based formulations are used for the management of multiple sclerosis in numerous countries, and CBD also received U.S. Food and Drug Administration approval for the treatment of refractory childhood epilepsy and glioblastoma multiforme. Herein, using a well-established mouse model of experimental autoimmune myocarditis (EAM) induced by immunization with cardiac myosin emmulsified in adjuvant resulting in T cell-mediated inflammation, cardiomyocyte cell death, fibrosis and myocardial dysfunction, we studied the potential beneficial effects of CBD. EAM was characterized by marked myocardial T-cell infiltration, profound inflammatory response and fibrosis (measured by quantitative real-time polymerase chain reaction, histology and immunohistochemistry analyses) accompanied by marked attenuation of both systolic and diastolic cardiac functions measured with a pressure-volume conductance catheter technique. Chronic treatment with CBD largely attenuated the CD3+ and CD4+ T cell-mediated inflammatory response and injury, myocardial fibrosis and cardiac dysfunction in mice. In conclusion, CBD may represent a promising novel treatment for managing autoimmune myocarditis and possibly other autoimmune disorders and organ transplantation.